Association between urinary incontinence and mortality risk among US adults: a prospective cohort study - Xuelan Peng; Yingjie Hu; Wenzhi Cai (BMC, 2024)
Abstract Background Urinary incontinence is frequent in the general population and affects men and women of all ages. UI carries an unsuspected load on the healthcare system. To investigate whether urinary incontinence is associated with all-cause, cardiovascular disease (CVD) and cancer mortality among US adults. Methods The analyzed data was collected from the 2007-2016 National Health and Nutrition Examination Survey (NHANES) data. A total of 25,182 US participants with complete information about follow-up information and urinary incontinence (UI) were included in this cohort study. Univariate Cox regression analyses, the UpSet plot, multivariate Cox regression analysis, subgroup analysis of all-cause mortality, and Kaplan-Meier survival curve were employed to support the research objectives. Results A total of 25,182 participants had a mean age of 49.8 ± 17.8 years, with 49.3% of them being male and 50.7% of them being female. In the unadjusted model, we found that the risk of all-cause mortality increased by 12% (95% CI 1.03-1.22, P = 0.008), the risk of CVD mortality increased by 21% (95% CI 1.07-1.36, P = 0.002), and the risk of Cancer mortality increased by 8% (95% CI 0.95-1.22, P = 0.243) among individuals with urinary incontinence. After adjusting for multiple variables, we found that the risk of all-cause mortality in patients with urinary incontinence decreased by 1% (95% CI 0.9-1.09), but this decrease was statistically insignificant (P = 0.868), and the risk of Cancer mortality decreased by 3% (95% CI 0.84-1.12, P = 0.686). The association between urinary incontinence and mortality risk were stable in stratified analyses. Conclusions In our study, we found that urinary incontinence itself is an independent risk factor for death. The association between urinary incontinence and mortality became less significant after adjusting for covariates, this is a common occurrence in statistical analysis. Future research, with larger sample sizes and more robust study designs, is needed to further elucidate the complex relationship between urinary incontinence and mortality risk.